2014
DOI: 10.1093/mnras/stu1312
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide intensity mapping at moderate redshifts

Abstract: We present a study of the feasibility of an intensity-mapping survey targeting the 115 GHz CO(1-0) rotational transition at z ∼ 3. We consider four possible models and estimate the spatial and angular power spectra of CO fluctuations predicted by each of them. The frequency bandwidths of most proposed CO intensity mapping spectrographs are too small to use the Limber approximation to calculate the angular power spectrum, so we present an alternative method for calculating the angular power spectrum. The models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 25 publications
1
103
0
Order By: Relevance
“…While the 21 cm reionization signal is brighter, the foregrounds are commensurately brighter because of the synchrotron spectral index, yielding a similar challenge. Considering CO (1-0) at 115 GHz, Breysse et al (2014) and Li et al (2015) suggest mean temperatures of 1 K m at z 3. The scales of interest at tens of arcminutes are reasonably analogous to the Cosmic Background Imager (CBI) (Pearson et al 2003), which finds fluctuations in the raw maps at the level of several hundred K m at 30 GHz.…”
Section: Review Of Continuum Foreground Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the 21 cm reionization signal is brighter, the foregrounds are commensurately brighter because of the synchrotron spectral index, yielding a similar challenge. Considering CO (1-0) at 115 GHz, Breysse et al (2014) and Li et al (2015) suggest mean temperatures of 1 K m at z 3. The scales of interest at tens of arcminutes are reasonably analogous to the Cosmic Background Imager (CBI) (Pearson et al 2003), which finds fluctuations in the raw maps at the level of several hundred K m at 30 GHz.…”
Section: Review Of Continuum Foreground Levelsmentioning
confidence: 99%
“…Intensity mapping was originally developed for 21 cm radiation (Hogan & Rees 1979;Scott & Rees 1990;Madau et al 1997), but has been studied for several other lines (in increasing frequency): deuterium (Sigurdson & Furlanetto 2006) (Righi et al 2008;Carilli 2011;Lidz et al 2011;Breysse et al 2014;Li et al 2015), C II (Gong et al 2012;Silva et al 2014;Uzgil et al 2014;Yue et al 2015), Lya Pullen et al 2014), C and O fine-structure (Kusakabe & Kawasaki 2012), and X-ray lines (Hütsi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that Breysse, Kovetz, & Kamionkowski (2014) (hereafter BKK) found that the amplitude of a CO intensity mapping power spectrum is extremely uncertain, and that different models yield very different results. We have every reason to believe that the modeling of each and every signal and foreground line we discuss here is similarly uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Line brightness determined through the cross-power does not have a cosmic variance or require a detailed model of the galaxy power spectrum. SWITZER Righi et al (2008) and Breysse et al (2014) have developed 2D anisotropy statistics for CO, and Pullen et al (2013) have considered cross-correlation with broadband CMB surveys. Mashian et al (2016) and Serra et al (2016) further calculate the global signal from CO and [C II] in the context of PIXIE.…”
Section: +023mentioning
confidence: 99%
“…STATISTICAL CONSTRAINTS ON THE ANISOTROPY Intensity mapping literature has described constraints primarily on the 3D power spectrum, which exploit unique tomographic capabilities (for 2D analysis, see e.g. Pullen et al 2013;Breysse et al 2014). PIXIE's 15 GHz bands give fewer modes in k than k ⊥ , and few total k modes for low-J CO transitions.…”
Section: Pixiementioning
confidence: 99%